Cancer Incidence Among Adolescents and Young Adults (15 to 29 Years) in Brazil. Issue 3 (April 2016) - Balmant, Nathalie V.; de Souza Reis, Rejane; Pinto Oliveira, Julio F.; Ferman, Sima; de Oliveira Santos, Marceli; de Camargo, Beatriz
Abstract : The spectrum of cancers commonly found in adolescents and young adults (AYAs) differs from those in children and adults; therefore, the childhood classification is not appropriate for this population. Here we used a newly proposed classification system to reclassify cases of AYAs from Brazilian population-based cancer registries (PBCRs) in 5 geographic regions of Brazil. We aimed to describe the cancer incidence rates within this age group according to PBCR. Using the world population, incidence rates per million were analyzed in each diagnostic subgroup according to sex and age at diagnosis (15 to 19 y, 20 to 24 y, and 25 to 29 y). The median incidence rate was 232.31 per million for females and 218.07 per million for males. Incidence increased with age, with the highest rate observed for 25- to 29-year-olds in both sexes. Carcinomas, lymphomas, and skin tumors were most frequent among AYAs. High incidence rates of cervix-uterus carcinoma were observed in most PBCRs. AYAs present epidemiological characteristics that differ from those of children, reinforcing the need for a new classification. This study describes, for the first time, the cancer incidence rate in AYAs in Brazil, and we believe that our findings represent the Brazilian profile. Abstract : Supplemental Digital Content is available in the text.